Testing Pecking Order Theory and Trade Off Theory on Consumer Goods Companies Listed on The Indonesia Stock Exchange in 2016-2020 - Hertanti, Delvi Krisda; Wardhianto, K Bagus (Jurnal Kompetitif Bisnis, 2022)
The purpose of this study is to examine two theories of capital structure, namely Pecking Order Theory and Trade Off Theory by examining the influence of profitability, company size, company growth, and asset structure on leverage. The sampling technique in this study used purposive sampling technique and obtained a sample of 19 companies listed on the Indonesia Stock Exchange for the period 2016-2020. The data analysis technique uses multiple regression analysis panel data model with the program test tool eviews 12. Based on the F (simultaneous) test, it shows that the variables of profitability, firm size, firm growth, and asset structure together have a simultaneous influence on leverage. Partially, it shows that the profitability variable has a significant and negative relationship towards leverage, the firm size variable has a significant effect and has a positive relationship direction towards leverage, the company growth variable has a significant and positive relationship towards leverage, and the asset structure variable does not. significant effect and has a negative relationship direction to leverage. Based on these results, the funding policy for consumer goods companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 is in line with the Pecking Order Theory capital structure theory.